2017
DOI: 10.1002/jsfa.8744
|View full text |Cite
|
Sign up to set email alerts
|

White clover fractions as protein source for monogastrics: dry matter digestibility and protein digestibility‐corrected amino acid scores

Abstract: A high digestibility of white clover protein was found irrespective of the physical fractionation. Together with a well-balanced amino acid composition, this makes white clover a promising protein source for monogastrics. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 39 publications
(85 reference statements)
0
41
1
1
Order By: Relevance
“…Compared to soybean meal commonly used in feed (Lagos and Stein, 2017), both ryegrass and red clover protein had well-balanced amino acid composition with favorable content of essential amino acids (Figure 8). Previous studies with proteins extracted from white clover, red clover and grass and precipitated by traditional methods obtained similar results and also documented good digestibility of the produced protein concentrates (Stødkilde et al, 2018(Stødkilde et al, , 2019. The effect of lignosulfonate on digestibility therefore remains to be investigated.…”
Section: Juice Clearing and Purity Of Protein Concentratementioning
confidence: 76%
See 1 more Smart Citation
“…Compared to soybean meal commonly used in feed (Lagos and Stein, 2017), both ryegrass and red clover protein had well-balanced amino acid composition with favorable content of essential amino acids (Figure 8). Previous studies with proteins extracted from white clover, red clover and grass and precipitated by traditional methods obtained similar results and also documented good digestibility of the produced protein concentrates (Stødkilde et al, 2018(Stødkilde et al, , 2019. The effect of lignosulfonate on digestibility therefore remains to be investigated.…”
Section: Juice Clearing and Purity Of Protein Concentratementioning
confidence: 76%
“…The soluble protein is separated from the juice and turned into a protein concentrate. Feeding trials with protein concentrate obtained from white clover, red clover, perennial grass and alfalfa have documented a high digestibility and a wellbalanced amino acid composition, which makes it a promising protein source for monogastrics (Stødkilde et al, 2018(Stødkilde et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, protein concentrates with slightly higher TP contents were produced from grass clover (35% DM) or red clover (40% DM) in laboratory setups . Moreover, protein concentrates produced by acid precipitation with sulfuric acid (pH = 4.0) at lab scale from the whole white clover plant presented CP content of 45% DM and TP contents of 39% DM, while higher CP content of 53% DM and higher TP content of 44% DM were achieved when the protein concentrate was produced only from white clover leaves . The protein concentrate presented a low pH (4.2) and had some lactic acid (6.1% DM), glucose (1.4% DM), and a considerable amount of inorganics (10.6% DM).…”
Section: Resultsmentioning
confidence: 99%
“…The chemical composition of the protein concentrate produced organically from grass clover biomass in the demon- clover plant presented CP content of 45% DM and TP contents of 39% DM, while higher CP content of 53% DM and higher TP content of 44% DM were achieved when the protein concentrate was produced only from white clover leaves. 34 The protein concentrate presented a low pH (4.2) and had some lactic acid (6.1% DM), glucose (1.4% DM), and a considerable amount of inorganics (10.6% DM). The concentration of each amino acid was slightly lower compared with the protein concentrates produced from clover grass and red clover in laboratory setups, 14 as shown in Table 4.…”
Section: Composition and Amino Acid Profile Of The Organic Protein Comentioning
confidence: 97%
“…The CP content in the final protein extract and protein digestibility have been shown to be affected by DM and CP content of the unprocessed plant (Pirie, 1978). Accordingly, Stødkilde et al (2018), Stødkilde et al (2019) showed in a rat model that protein extraction improved digestibility compared to the unprocessed plant. The AA composition in the protein extract was well balanced from a nutritional point of view, and the content of methionine was superior to the content in soybean and soybean meal (National Research Council, 2012;SEGES Svineproduktion, 2018) and to earlier findings on white clover, red clover and lucerne (Damborg et al, 2018;Stødkilde et al, 2018Stødkilde et al, , 2019.…”
Section: Composition Of Protein Extract Produced From Grass-clovermentioning
confidence: 99%